2023
DOI: 10.3389/fmolb.2023.1073770
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a polyamine-related signature and six novel prognostic biomarkers in oral squamous cell carcinoma

Abstract: Elevated polyamine levels are required for tumor transformation and development; however, expression patterns of polyamines and their diagnostic potential have not been investigated in oral squamous cell carcinoma (OSCC), and its impact on prognosis has yet to be determined. A total of 440 OSCC samples and clinical data were obtained from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). Consensus clustering was conducted to classify OSCC patients into two subgroups based on the expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Oral squamous cell carcinoma is one of the most common malignancies worldwide, 24 and its morbidity and mortality in China are increasing annually. 25 HNSCC patients. 28 However, many patients are either intrinsically resistant to these regimens (chemotherapy, targeted therapy or immunotherapy) or develop acquired resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral squamous cell carcinoma is one of the most common malignancies worldwide, 24 and its morbidity and mortality in China are increasing annually. 25 HNSCC patients. 28 However, many patients are either intrinsically resistant to these regimens (chemotherapy, targeted therapy or immunotherapy) or develop acquired resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Oral squamous cell carcinoma is one of the most common malignancies worldwide, 24 and its morbidity and mortality in China are increasing annually 25 . Surgery or definitive radiotherapy (RT) is used to treat OSCC patients at the early stages, and the majority of the patients have a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although risk stratification based on the SMLs can better predict the survival and clinical outcomes of patients with PAAD, it cannot distinguish populations with different TIME characteristics. Studies have shown that tumor subgroups derived from consensus clustering analysis have different TIME characteristics and impact immunotherapy response [ [66] , [67] , [68] ]. Accordingly, we performed a consensus clustering analysis based on the constructed SMLs, dividing the TCGA-PAAD cohort into two clusters to further explore the differences in clinical outcomes and the TIME of patients in different subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of polyamines is tightly regulated, and any disruption of polyamine levels is associated with various diseases, including cancer, where polyamine levels are frequently elevated [30,31]. Furthermore, elevated polyamine levels are also linked to age-related diseases such as PD and AD [67,100].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the plethora of functions of metabolites such as Pas, they can be considered disease indicators. For example, in cancer, they have been widely used in diagnosis and as markers of tumor progression, as cancer patients have elevated levels of polyamines [30][31][32][33][34]. As such, there is more than one reason to consider polyamines as novel biomarkers that could indicate the progression of age-related diseases.…”
Section: Polyamines As Novel Biomarkers For Age-related Diseasesmentioning
confidence: 99%